Hábitos de consumo de YouTube en los jóvenes de la Universidad Técnica de Cotopaxi. - Portilla Achig, Valeria Samantha (2020)
YouTube platform has become an important social network worldwide, however there are insufficient researches in local contexts; Therefore, this Project has as main objective to categorize consumption habits in young people of the Universidad Technical de Cotopaxi. The methodological strategy that was implemented had a quantitative approach, using survey techniques; The instrument applied was a questionnaire with 18 ítems, which was developed base don the objectives, set out within the project and it was applied at 6 faculty careers: Basic Education, Initial Education, Communication, Language Pedagogy, Social Work and Computer Graphic Design. Among the main results the most researched content by young people is music, movies and tutorials, stands out. Another of the obtained results was young people consider advertising that is broadcast at this platform as invasive. In addition, users Access this network mainly bu smartphones or laptops. Among the main conclusions it is noted that this platform has changed its functions over time, YouTube has become a lucrative website for companies and youtubers and less attractive to the consumer